ArchiRev—Reverse engineering of information systems toward ArchiMate models. An industrial case study. Issue 2 (15th September 2020) - Pérez‐Castillo, Ricardo; Caivano, Danilo; Ruiz, Francisco; Piattini, Mario
Abstract: In the context of digital transformation, companies are increasingly forced to develop, manage and continually align IT and business. Companies have found in Enterprise Architecture (EA) a valuable tool to represent and manage IT and business in a holistic way by establishing connections among technology concerns and business/strategical/motivational ones. EA modelling is one of the most critical tasks in this context to represent accurate models that make the difference in the decision‐making and governance processes of the company. In most of the cases, EA models are manually defined by experts which is usually error‐prone and time‐consuming. Thus, the constant business and IT realignment through manual modelling becomes complex and expensive. This research presents ArchiRev, an extensible reverse engineering method that automate the extraction of EA models (using ArchiMate language) by analysing different information systems artefacts. This proposal has been validated through an industrial case study in the context of a C#‐based system of an Italian ship refurbishment company. The study has demonstrated the effectiveness (based in the opinion of some business experts) and efficiency of the method. The main implication is that EA modelling can be accelerated, whereas subjectivity and errors introduced by experts might be reduced.